Daniel Tiger's neighborhood. Daniel goes camping [videorecording (DVD)] (PBS Kids, 2016)
Four-year-old Daniel Tiger invites young viewers directly into his world; giving them a kid's eye view of his life and making them feel like one of his neighbors.